Temperature-dependent transport mechanisms through PE-CVD coatings: comparison of oxygen and water vapour. (4th September 2017) - Kirchheim, D; Wilski, S; Jaritz, M; Mitschker, F; Gebhard, M; Brochhagen, M; Böke, M; Benedikt, Jan; Awakowicz, P; Devi, A; Hopmann, Ch; Dahlmann, R
Abstract: When it comes to thin coatings such as plasma-enhanced chemical vapour deposition or plasma-enhanced atomic layer deposition coatings on substrates of polymeric material, existing models often describe transport through these thin coatings as mainly driven by transport through defects of different sizes. However, temperature-dependent measurements of permeation could not confirm this hypothesis and instead gaseous transport through these thin coatings was found to more likely to occur through the molecular structure. This paper correlates existing transport models with data from oxygen transmission experiments and puts recent investigations for water vapour transmission mechanisms into context for a better understanding of gaseous transport through thin coatings.